Sistem Monitoring Tanaman Hidroponik Berbasis Iot (Internet of Thing) Menggunakan Nodemcu ESP8266 - Doni, Rahmad; Rahman, Maulia (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
This Hydroponic Plant Monitoring System was created using Nodemcu ESP8226, which supports internet access. So that the monitoring process can be done through an android application. Plant data is obtained through the DHT11 sensor and Water Sensor, which is then processed using the Fuzzy method to determine the time to water the plants and add water to the hydroponic plant storage tank. From the results of sensor readings, the system can determine the time to water the plants according to weather conditions and send warnings when the water in the storage tank is less than the predetermined condition.